Going vertical: examining the rise and impact of contemporary Russian sports cinema - Crosson, Seán (Frontiers in Sports and Active Living, 2023)
Introduction While Hollywood has been central to the definition and popularisation of the genre internationally, sport cinema also has a significant presence in national cinemas across the world, though less research has been undertaken to date of the place of sport within European cinema and its growing importance in this context. This article will introduce a new database and online research platform (Sport in European Cinema, sportandfilm.eu) recently made publicly available which enables a deeper consideration of the significance of sport in European cinema, including its increasing importance in the Russian context. Indeed the third most commercially successful indigenous film ever released (as of 2023) at the Russian box office is a sports film, Движение вверх (Going Vertical (AKA Three Seconds) (2017). Methods This article adopts a mixed-methods approach, combining quantitative and qualitative methods to examine the place of sport in European cinema, including a case study of contemporary Russian sport cinema and its connection with broader political and ideological messaging. Results Sport cinema has become an increasingly important part of European cinema, both in terms of number of films produced and their impact on European society, as evident in the case study provided of Russian sport cinema. Conclusion This paper introduces a new research database dedicated to European Sport Cinema and identifies the increasing importance of sport cinema in the European context. It includes a case study of contemporary Russian sport cinema and identifies its role in articulating and affirming existing power structures and ideological hegemony within Russian society, as evident within Going Vertical and further recent Russian sport films in a particularly challenging period of national and international instability and contestation.